2007
DOI: 10.1007/s10265-007-0076-1
|View full text |Cite
|
Sign up to set email alerts
|

Natural hybridization origin of Rhododendron agastum (Ericaceae) in Yunnan, China: inferred from morphological and molecular evidence

Abstract: The natural hybridization that occurs between two sympatric species of Rhododendron subgenus Hymenanthes in Yunnan, China, was investigated. The assumed parents, Rhododendron delavayi Franch. and R. decorum Franch., are morphologically distinct, and the putative hybrid species, R. agastum Balf. f. et W. W. Smith, has an intermediate morphology. We used the main morphological characters, sequences of the nuclear ribosomal DNA ITS region, and the chloroplast DNA trnL-F intronspacer to analyze the three species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…Interestingly, analysis of the nucleotide additive patterns of these putative hybrid samples revealed that they were likely to have arisen from the combination between the individual sequences of the STEL Type A and the STEL Type B at most nucleotide additive sites. These results of ITS nucleotide additive sequences in C. stellatopilosus were similar to those of previous reports on the hybridization of Paeonia [11] and Rhododendron agastum [12]. Based on the appearance of two individual and the additive nucleotides of the obtained ITS sequences, we propose that hybridization of the two types occurred in C. stellatopilosus species.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, analysis of the nucleotide additive patterns of these putative hybrid samples revealed that they were likely to have arisen from the combination between the individual sequences of the STEL Type A and the STEL Type B at most nucleotide additive sites. These results of ITS nucleotide additive sequences in C. stellatopilosus were similar to those of previous reports on the hybridization of Paeonia [11] and Rhododendron agastum [12]. Based on the appearance of two individual and the additive nucleotides of the obtained ITS sequences, we propose that hybridization of the two types occurred in C. stellatopilosus species.…”
Section: Resultssupporting
confidence: 91%
“…However, homoploid hybridization is more difficult to recognize than hybridization accompanying polyploidization (Grant 1981;Ferguson and Sang 2001). Several cases of natural homoploid hybridization have been demonstrably proved by the phylogenetic method and most are referred to as diploid (e.g., Rieseberg 1995;Howarth and Baum 2005;Pan et al 2007;Yamaji et al 2007;Zhang et al 2007). To date, tetra-homoploid hybridizations have been found in a few species (Ferguson and Sang 2001;Nagamitsu et al 2006).…”
Section: Introductionmentioning
confidence: 96%
“…delavayi ), and suggested R. decorum was the other parent. While it is true that an artificial hybrid of these two species does exhibit certain morphological similarities with ‘ R. agastum ’ (Zhang et al 2007; Zha et al. 2008), further genetic and morphological work showed convincingly that it is a hybrid of R. delavayi and R. irroratum (Zha et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…That hybridization occurs frequently in Rhododendron is well-accepted and extensive evidence of natural hybrid formation can be found across the genus (Kron 1997; Milne et al 2003; Zhang et al 2007; Milne and Abbott 2008; Zha et al 2008; Marczewski et al 2015). Moreover, hybrids can occur between species in different subsections [e.g.…”
Section: Introductionmentioning
confidence: 94%